Dipnoan from the Upper Triassic of East Greenland and remarks about palaeobiogeography of Ptychoceratodus - Pawlak, Wojciech; Tałanda, Mateusz; Sulej, Tomasz; Niedźwiedzki, Grzegorz (Endocrine Abstracts, 2020)
Pawlak, Wojciech, Tałanda, Mateusz, Sulej, Tomasz, Niedźwiedzki, Grzegorz (2020): Dipnoan from the Upper Triassic of East Greenland and remarks about palaeobiogeography of Ptychoceratodus. Acta Palaeontologica Polonica 65 (3): 561-574, DOI:10.4202/app.00679.2019, URL: http://dx.doi.org/10.4202/app.00679.2019